Politics of India since Independence - "Brass, Paul R." (Cambridge, 2006)
The Politics of India since Independence provides a comprehensive study of the major political, cultural, and economic changes in India since gaining independence. Paul Brass focuses on the consequences of the centralising drives of the national leadership to create a strong, unified nation, and a dynamic economy, all of which have been put into jeopardy in recent years by increased inter-caste conflicts, the rise of militant Hindu nationalism, and the worst communal massacres since Independence. In the second edition of his book, the author takes account of recent events to ask whether the country can find the right leadership to restore a political and communal balance in state and society.
Keywords: India-Politics and government-1947